The Comparison of Factors Affected to Labor Mobility in Eastern Seaboard Industrial Area - ลือกิตินันท์, วรรณภา (Business Administration and Management Journal Review, 2016)
The research aimed to compare the opinions about the factors affected to labor mobility in industrial area of the Eastern Seaboard by personal factors; gender, age and marriage status. The author gathered the data from 385 migrant workers in industrial area of the Eastern Seaboard by questionnaires. The statistics used for data analysis were frequency, percentage, average, standard deviation, t-Test and ANOVA. The findings found that the majority of respondents were female, aged between 26-32 years old, single and resident in the Northeast of Thailand. The opinions about the factors affected to labor mobility in the highest rank were the desire of income increasing and the lowest rank were the previous occupation failure. Regarding to compare the opinions by gender, age and status, the opinions were indifferent. The males would seek job security, while females were relocating in order to family or spouse. For the widowed and the divorced, previous occupation failure factor affect to labor mobility on a massive scale. Moreover, the labors of all ages have the different opinions on seven factors affected to labor mobility, except the desire of income increasing.